STANDARDISASI SPESIFIK DAN NON SPESIFIK EKSTRAKSI HIDROTROPI ANDROGRAPHOLID DARI SAMBILOTO (Andrographis paniculata) - Rita Dwi Ratnani; Indah Hartati; Yance Anas; Devi Endah P.; Dita Desti D_Khilyati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Several active compounds has been found in Andrographis paniculata, including andrographolide (deoxy andrographolide, andrographolide, neo andrographolide and 14-deoxy-11,12-didehydroandrographolide) and kalmeghin. The active compounds properties and its levels in extract medicinal plants cannot be guaranteed to always be in a constant amount. This may be due to variations in the quality of medicinal plants, such as seeds, grow location, climate, conditions (age and harvest method), as well as post-harvest process and extraction method. Therefore, standardization of the extract should be performed to ensure the quality of the extract before it is produced on an industrial scale. The purpose of this study is to standardize the sambiloto hydrotropic extract. Specific parameters such as the organoleptic properties of the extract and identification of andrographolide compound as marker compounds. In contrast, the non-specific parameter includes drying shrinkage, microbiological contamination levels, heavy metal contamination levels, ash levels, the solubility of extracts in water and ethanol. The results showed that the organoleptic properties hydrotropic sambiloto extract are in powder form dense, dry, dark green, characteristic odor and bitter taste. Andrographolide compound as a marker compound in the sambiloto extract was identified by TLC method. The non-specific parameters of sambiloto hydrotropic extract were shrinkage drying of 13.5%, microbiological contamination of (3.1x107) CFU/g, heavy metal contamination (Cd levels of 0.104 ppm, and Pb levels of 2.248 ppm), ash levels of 37.5%, and the solubility extracts in water and ethanol are 40.8 % dan 42.0% respectively. Key words: Andrographis paniculata, extract standardization, specific and non-specific